Influence of bed height and drying temperature on shrimp drying characteristics using a fluidized-bed dryer - K. Nanan; Smith Eiamsa–ard; S. Chokphoemphun; Manoj Kumar; Monsak Pimsarn; V. Chuwattanakul (Case Studies in Thermal Engineering, 2023)
The aim of this work was to study shrimp drying in a fluidized-bed dryer to develop a process that performs better than traditional (sun dried) shrimp production. In these experiments, the influence of shrimp size (small, medium and large), bed height (h/D = 0.33, 0.66 and 1.0) and air temperature (60, 70 and 80 °C) on the drying rate were studied under a constant blower power. The experimental results showed that the moisture content of boiled shrimp decreased with an increased drying temperature due to the consequently higher temperature differential between the hot air and the shrimp. When the bed height (h/D) was reduced, shrimp moisture removal increased, but it also increased when shrimp size decreased. Moreover, the production rate of dried shrimp under a bed height h/D = 1.0 and drying temperature of 80 °C yielded the highest dried shrimp production rate of 4.83, 4.21 and 3.72 kg/h for small, medium and large shrimps, respectively.
Keywords: Food Drying and Modeling; Microencapsulation and Drying Processes; Meat and Animal Product Quality